2014
DOI: 10.1016/j.jcrs.2013.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Patient and surgeon experience during laser in situ keratomileusis using 2 femtosecond laser systems

Abstract: Patients preferred surgery with the 500 kHz laser with no loss of light perception, less pain, less fear, and less subconjunctival hemorrhage. Surgeons preferred the 60 kHz laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…13 However, a contralateral eye study of LASIK with the Intralase 60-kHz laser and VisuMax 500-kHz laser reported that patients experienced docking and suction as more frightening with the 60-kHz laser. 10 The reported fear scores for the LASIK 500-kHz group were comparable to our current findings. Because the intraoperative intraocular pressure during suction is higher with the 60-kHz laser than with the 500-kHz laser, it may cause more fear in the patients, whereas the intraoperative intraocular pressure is the same in LASIK and SMILE.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…13 However, a contralateral eye study of LASIK with the Intralase 60-kHz laser and VisuMax 500-kHz laser reported that patients experienced docking and suction as more frightening with the 60-kHz laser. 10 The reported fear scores for the LASIK 500-kHz group were comparable to our current findings. Because the intraoperative intraocular pressure during suction is higher with the 60-kHz laser than with the 500-kHz laser, it may cause more fear in the patients, whereas the intraoperative intraocular pressure is the same in LASIK and SMILE.…”
Section: Discussionsupporting
confidence: 88%
“…This prospective, randomized, paired-eye study aimed to evaluate the intraoperative and postoperative patient experience in LASIK and SMILE by a standardized validated questionnaire. 2,10 Patients experienced more discomfort during tissue manipulation in SMILE than flap lifting in LASIK, whereas docking and laser application seemed equally uncomfortable for the patients. Interestingly, the patients still feared the initial docking and suction more in LASIK than SMILE, although the level of discomfort was similar for the two refractive procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations